A young woman with acute coronary syndrome and antiphospholipid syndrome. Is it the antiphospholipid syndrome or COVID-19 vaccination or classical risk as the risk factor? a case report - Sisca Natalia Siagian; Christianto Christianto (Journal of Medical Case Reports, 2024)
Abstract Background Acute coronary syndrome (ACS) in young women is poorly understood due to underdiagnosis and undertreatment. One of the possible risk factors for ACS in young women is antiphospholipid syndrome (APS). Coronavirus disease 2019 (COVID-19) vaccination also emerged as one of the possible risk factors for ACS during the COVID-19 pandemic. Case presentation Our patient, a 39-year-old Batak woman with dyslipidemia and family history of cardiovascular disease, experienced chest pain slightly improved at rest accompanied by autonomic symptoms. She was diagnosed with non-ST-elevation myocardial infarction (NSTEMI) based on her clinical features, dynamic electrocardiogram changes, troponin elevation, and multislice computed tomography angiography confirmed with diagnostic catheterization. The patient was managed by percutaneous coronary intervention with implantation of drug-eluting stents. On follow-up, the patient was diagnosed with APS based on history of preeclampsia with severe features in the first and third pregnancy, spontaneous abortion in the second pregnancy, history of transient ischemic attack, moderately positive lupus anticoagulant on two occasions with an interval of 12 weeks, and ACS. Further investigation revealed a history of COVID-19 vaccination with Sinovac four and six weeks before presentation. The patient was recommended for lifelong warfarin and short-term dual antiplatelet (aspirin and ticagrelor). Conclusions Young women are not completely immune to ACS as evident in this case of ACS in a young woman with classical risk factors (dyslipidemia and family history of cardiovascular disease) and APS. Further studies are required to fill the knowledge gap on whether COVID-19 vaccination had any contribution to the ACS in the young woman.